2004
DOI: 10.1074/jbc.m404113200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approximation between a Residue in the Amino-terminal Region of Calcitonin and the Third Extracellular Loop of the Class B G Protein-coupled Calcitonin Receptor

Abstract: The calcitonin receptor is a member of the class B family of G protein-coupled receptors, which contains numerous potentially important drug targets. Delineation of themes for agonist binding and activation of these receptors will facilitate the rational design of receptor-active drugs. We reported previously that a photolabile residue within the carboxyl-terminal half (resi- Calcitonin (CT), 1 secreted by the thyroid gland in response to elevations in blood calcium levels, is a peptide hormone that regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 59 publications
(91 reference statements)
8
56
0
Order By: Relevance
“…However, another two carboxyl-terminal position 23 and 28 probes were shown to label the distal amino terminus (49,50). The labeling of the calcitonin receptor is quite consistent with the data from the secretin and PTH receptors (44,51), but the labeling of the VPAC1 receptor suggests a different mechanism. All the vasoactive intestinal polypeptide (VIP) probes tested so far label the amino-terminal domain adjacent to the transmembrane domain.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…However, another two carboxyl-terminal position 23 and 28 probes were shown to label the distal amino terminus (49,50). The labeling of the calcitonin receptor is quite consistent with the data from the secretin and PTH receptors (44,51), but the labeling of the VPAC1 receptor suggests a different mechanism. All the vasoactive intestinal polypeptide (VIP) probes tested so far label the amino-terminal domain adjacent to the transmembrane domain.…”
supporting
confidence: 77%
“…Based on these studies, a "two-step" or "tethering" mechanism has been proposed, where the carboxyl-terminal region of the peptide ligand initially interacts with the amino-terminal domain of the receptor, and in the second step, the amino-terminal region of the ligand interacts with the core domain of the receptor, which leads to receptor activation (27). This mechanism has also been proposed for other members of Family B GPCRs (42)(43)(44). Our current data show that both the position 24 and 35 residues of GLP1 are in proximity with the residues in the amino-terminal domain of its receptor, which is consistent with this mechanism.…”
mentioning
confidence: 99%
“…Each receptor possesses a characteristically large and sequence-divergent extracellular N-terminal domain; however, there is conservation of key residues, including three disulfide bonds within this domain, that aids in stability and confers similarities in secondary structure (3,4). The widely accepted peptide-receptor binding model for family B GPCRs is the two domain model, whereby the ␣-helical C terminus of the endogenous ligand interacts with the N-terminal domain of the receptor, and the N terminus of the peptide interacts with the core domain of the receptor, which includes both the extracellular loops and TM bundle (5)(6)(7). Generically, the N-terminal domain of the receptor is primarily responsible for ligand recognition and specificity, whereas the core of the receptor has a major influence in signaling specificity and transmission (8).…”
Section: Gpcrsmentioning
confidence: 99%
“…In human CT (hCT), amino acid 16, located one helical turn apart from residue 19, cross-linked to Phe 137 , consistent with orientation of the ␣-helix of agonist peptides with the membrane-proximal region of the receptor amino terminus (46). We have also demonstrated that hCT amino acid 26 interacts with Thr 30 in the distal amino terminus (46), whereas hCT amino acid 8 interacts with Leu 368 in the third extracellular loop (47).…”
Section: Calcitonins (Cts)mentioning
confidence: 77%